The Mapping Of Shoreline Change Caused By Accretion And Abration As An Impact Of Tin Minning In Pangkalpinang - Akhrianti, Irma; Nugraha, Moh Agung; Gustomi, Andi; Arizona, Mohammad Oka (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2024)
ABSTRACTBangka Island is the biggest tin producer in Indonesia. Pangkalpinang is the capital city of Bangka Belitung Archipelago which has 36 km2 shoreline and is one of the areas affected by anthropogenic activities especially tin minning activities. This study aims to determine the changes of position and rate of shoreline change in 2000 – 2022 using multitemporal imagery in Pangkalpinang. This study used remote sensing method (Algorhytm of Normalized Difference Water Index) and geographic information system with on screen digitation approach using DSAS (Digital Shoreline Analysis). Shoreline position measurement using the NSM analysis and rate of shoreline change using the EPR analysis. Digital image processing result showed that shoreline position at coastal region in Pangkalpinang has changed in 22 years. At sector A (Pasir Padi area), The land mass accretion/ maximum accretion occurred at Serata, Pasir Padi Beach adjacent to Batu Rusa estuary which was 63,6 m with shoreline rate change was approximately 2.89 m/year, while the land mass decreasement/ highest abration occurred in Pasir Padi Beach was 164,5 m with the shoreline rate change was approximately 7.48 m/ year. At sector B (Tanjung Bunga Area) abration occurred was -124.6 m with the shoreline rate change was approximately 5.66 m/year. At sector C (Sampur Beach Area) abration occurred was 81 m with shoreline rate change was 3.68 m/tahun. The average of shoreline change rate in Pangkalpinang affected by abration was 2.5 m/year while the average of shoreline change affected due to accretion was 2.89 m/year whereas there were 2 beaches in Pangkalpinang which did not experience the accretion, namely Tanjung Bunga Beach and Sampur Beach.Keywords: Shoreline, Pangkalpinang, Accretion, Abration, Tin Minning